2020
DOI: 10.3390/w12030859
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the MONERIS Nutrient Emission Model for a Lowland Country (Hungary) to Support River Basin Management Planning in the Danube River Basin

Abstract: The contamination of waters with nutrients, especially nitrogen and phosphorus originating from various diffuse and point sources, has become a worldwide issue in recent decades. Due to the complexity of the processes involved, watershed models are gaining an increasing role in their analysis. The goal set by the EU Water Framework Directive (to reach “good status” of all water bodies) requires spatially detailed information on the fate of contaminants. In this study, the watershed nutrient model MONERIS was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The goal set by the EU Water Framework Directive to reach "good status" for all water bodies requires spatially detailed information on the fate of contaminants. In a study by Jolánkai et al [19], the watershed nutrient model MONERIS was applied to the Hungarian part of the Danube River Basin. The spatial resolution was 1078 water bodies (mean area of 86 km 2 ), and two subsequent 4 year periods (2009-2012 and 2013-2016) were modeled.…”
Section: Monitroing Modeling and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal set by the EU Water Framework Directive to reach "good status" for all water bodies requires spatially detailed information on the fate of contaminants. In a study by Jolánkai et al [19], the watershed nutrient model MONERIS was applied to the Hungarian part of the Danube River Basin. The spatial resolution was 1078 water bodies (mean area of 86 km 2 ), and two subsequent 4 year periods (2009-2012 and 2013-2016) were modeled.…”
Section: Monitroing Modeling and Managementmentioning
confidence: 99%
“…The study revealed that (i) digital-filter-based separation of surface and subsurface runoff yielded different values for these components, but this change did not influence nutrient loads significantly; (ii) shallow groundwater phosphorus concentrations in the sandy soils of Hungary differ from those of the MONERIS default values; (iii) a significant change of the phosphorus in-stream retention parameters was needed to approach measured in-stream phosphorus load values. Local emissions and pathways were analyzed and compared with previous model results [19].…”
Section: Monitroing Modeling and Managementmentioning
confidence: 99%
“…A cross-sectoral approach is used to try to reach the goals of the WFD, point sources, such as wastewater treatment plants got regulated, policies have been drafted to deal with diffuse sources such as agriculture; however, some natural factors, such as bird migration or the winter slowdown of microbial activity, are typically not taken into consideration. Nitrogen and phosphorus play a dominant role in the degradation of water quality in lakes, streams, and wetlands and are thus factors of key importance when classifying water quality according to the framework (Jolánkai et al 2020;Yang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a promising approach to estimating total diffuse load its development requires an overview of monitoring stations. Although this is a promising approach to better estimate the total diffuse loads, it requires a review of monitoring stations due to flow calibration (Jolánkai et al, 2020). The average annual evaporation rate is expected to increase slightly over the 21st century (Csáki et al, 2020), while in the case of runoff, a significant decrease is expected, which will involve changes in loads from urban areas.…”
Section: Introductionmentioning
confidence: 99%